USER SATISFACTION PERCEPTION OF BCA MOBILE BANKING SERVICES: A SURABAYA YOUTH PERSPECTIVE - Zulfa, Vivi Rodliyatuz; Kristanto, Damar; Permatasari, Maurisia Putri; Ervianty, Rizka Miladiah; Salam, Moh. Darus; Fiatiano, Edwin; Dwikesumasari, Phima Ruthia (Journal of Innovation Research and Knowledge, 2026)
Mobile banking has fundamentally reshaped the interaction between individuals and finansial institutions by providing uninterrupted and convenient access to wide range of banking services. In addition to improving efficiency, mobile banking as a critical tool for advancing financial inclusion, particularly among populations historically underserved by traditional banking systems, such as those residing in rural regions or low-income communities. Millennials, characterized by their rapid adoption of digital technologies, have increasingly integrated mobile banking into their routine financial activities to support their fast-paced lifestyles. BCA Mobile significantly contributes to shaping service standards and digital innovation. Continuous evaluation of user satisfaction is important to ensure that the application remains relevant and responsive to evolving user needs, especially in terms of interface quality and overall user experience. This study aims to examine the satisfaction levels of millennial users in Surabaya toward BCA Mobile. A total of 542 respondents provided their perceptions of the platform’s features and services. The findings indicate that most service aspects fall within the “good” satisfaction category; however, none reached the “very good” level. These results underscore the need for further enhancement of BCA Mobile’s features and service quality, particularly to better align with the expectations of millennial users